2005
DOI: 10.1002/app.22365
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan application on wool before enzymatic treatment

Abstract: ABSTRACT:The influence of a chitosan application on wool fabric before a treatment with a proteolytic enzyme has been investigated. The enzymatic treatment enhances whiteness and confers shrink resistance to wool, but an increase in the enzyme concentration leads to a detrimental effect on the physicomechanical properties. A chitosan treatment before the enzymatic treatment additionally improves the shrink resistance and increases the weight loss. To better investigate the role played by the chitosan, surface-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Previous studies [15] observed some interfibre CHT bonding, which was assumed to prevent movement of fibres and reducing shrinkage. Such deposition of CHT on the wool fibre surface and interfibrillar bonding could prevent fibres escape the fabric structure, therefore exerting a protective function and preventing pilling formation.…”
Section: Colour Changementioning
confidence: 97%
“…Previous studies [15] observed some interfibre CHT bonding, which was assumed to prevent movement of fibres and reducing shrinkage. Such deposition of CHT on the wool fibre surface and interfibrillar bonding could prevent fibres escape the fabric structure, therefore exerting a protective function and preventing pilling formation.…”
Section: Colour Changementioning
confidence: 97%
“…1.9(d)), resulting in a smoother surface and deeper inter-fibrillar disintegration of the bundle. The influence of a chitosan application on wool fabric before a treatment with a proteolytic enzyme was investigated by Vílchez et al 39 The enzymatic treatment enhances whiteness and confers shrink resistance to wool, but an increase in the enzyme concentration leads to a detrimental effect on the physico-mechanical properties. A chitosan treatment before the enzymatic treatment was also found to improve the shrink resistance and increase the weight loss.…”
Section: Recent Studies On the Modification Of Textilesmentioning
confidence: 99%
“…However, if not carefully controlled this enzymatic process can cause significant damage to the wool fibre due to the enzyme penetrating into and attacking the fibre core [2,3]. To restrict the enzyme attack to the cuticle scales and prevent damage to the fibre, methods of either modifying the treatment process [4][5][6][7] or enlarging the proteolytic enzyme by chemical [8][9][10] or genetic modification [11] have been investigated but a viable commercial process is not currently available.…”
Section: Introductionmentioning
confidence: 99%